Production and spectroscopy of cold radioactive molecules - Chandler J. Conn; Phelan Yu; Madison I. Howard; Yuxi Yang; Chaoqun Zhang; Arian Jadbabaie; Aikaterini Gorou; Alyssa N. Gaiser; Timothy C. Steimle; Lan Cheng; Nicholas R. Hutzler (Science, 2026)
Molecules with heavy, radioactive nuclei promise extreme sensitivity to fundamental nuclear and particle physics. However, these nuclei are available in limited quantities, which challenges their use in precision measurements. Here we demonstrate the gas-phase synthesis, cryogenic cooling, and high-resolution laser spectroscopy of radium monohydroxide, monodeuteroxide, and monofluoride molecules ( 226 RaOH, 226 RaOD, and 226 RaF) in a tabletop apparatus by combining trace radioactive target production protocols, optically driven chemistry in a cryogenic buffer gas, and low-background spectroscopic detection methods. The molecules are cooled in the lab frame, creating conditions that are the same starting points as those for many current molecular precision measurement and quantum information experiments. This approach can be readily applied to a wide range of species and establishes key capabilities for molecular quantum sensing of exotic nuclei.